Immigrant-native differences in stockholding: The role of cognitive and non-cognitive skills - Marc-André Luik; Max Friedrich Steinhardt (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2015)
This paper provides new evidence on native-migrant differences in financial behavior by analyzing the role of noncognitive and cognitive skills. We make use of data from the Health and Retirement Survey (HRS) which is a longitudinal household survey of the older U.S. population containing detailed information about demographic characteristics, financial assets and personality traits of household members. In line with previous studies, we find a substantial gap in stockholding between immigrant and native households. Estimates from a random effects model suggest that cognitive and non-cognitive skills, including personality concepts and economic preferences, are important drivers of stockholding and explain part of the differences between natives and immigrants. These findings are supported by results from a Blinder-Oaxaca decomposition analysis. Our paper therefore delivers first evidence that differences in non-cognitive and cognitive skills contribute to the explanation of the financial market participation gap between natives and immigrants.
Keywords: D14; G02; G11; J61; 330; Stockholding; Immigrants; Personality traits; Decomposition